PENGARUH PROFITABILITAS, LIKUIDITAS TERHADAP DIVIDEND PAYOUT RATIO PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Perusahaan Bluechip yang Terdaftar di Bursa Efek Indonesia 2012-2016) - Nala Tri Kusuma (Universitas Ahmad Dahlan, 2019)
The purpose of this study is to describe (1) Effect of Profitability on Dividen Payout Ratio at Bluechip company period 2012-2016. (2) Liquidity Influence on Dividen Payout Ratio at Bluechip company period 2012-2016. (3) The Influence of Profitability to Good Corporate Governance at Bluechip Company for the period of 2012 - 2016. (4) Influence of Liquidity to Good Corporate Governance at Bluechip Company in 2012-2015. (5) Influence of Good Corporate Governance to Dividen Â Payout Ratio at Bluechip company period 2012-2016.The sample of this research is 10 companies selected by using purposive sampling method. The data analysis used is multiple linear regression to identify independent variables that influence the dependent variable and path analysis to detect indirect influence through good corporate governance.The result of this study indicate (1) Profitability has a significant effect on Good Corporate Governance, (2) Liquidity does not affect Good Corporate Governance, (3) Profitability has a significant effect to Dividen Â Payout Ratio (4) ) Liquidity has a significant effect to Dividen Payout Ratio, (5) Good Corporate Governance has no effect to Dividen Payout Ratio.